POLLINATION AND FRUITING OF FLOWERS OF THE LINDEN SPECIES (TILIA TOMENTOSA) INTRODUCED INTO THE FERGANA URBAN FLORA (Scientific journal of the Fergana State University, 2024)
Currently, in the Ferghana climate, the cultivation of lime trees from other places leads to the creation of high-yielding varieties and forms here by acclimatization and seed production, crossing long-lived forms by their reproduction by biotechnological methods and use as a honey plant or in forestry, as well as in agriculture from an embryological point of view, the formation of generative organs, development, microsporogenesis and mesosporogenesis, double fertilization, and the study of aspects such as endospermogenesis and embryogenesis are also becoming important.